2010
DOI: 10.1111/j.1600-0706.2010.18955.x
|View full text |Cite
|
Sign up to set email alerts
|

Which are the phenologically flexible species? A case study with common passerine birds

Abstract: One of the most consensual ecological effects of the current climate warming is the alteration of the environmental timing of ecosystems. Phenological shifts, at different levels of food webs, are predicted to have major effects on species assemblages. Indeed it is unlikely that all species should be able to respond to the phenological shifts of their environment evenly. Yet questions remain about the specific traits that predict the ability of a species to track the temporal fluctuations of its environment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…However, recently published studies from the northern hemisphere provide useful pointers for future investigations. Amongst passerines in France, for example, species with the broadest ecological and thermal niches, shortest mean migration distances and largest brains were most able to adjust their phenology, indicating that specialists and long distance migrants are more at risk [84]. The migration of Barn Swallows Hirundo rustica from southern Africa appears to be constrained by the need to complete their moult before leaving their non-breeding grounds [27], [85].…”
Section: Discussionmentioning
confidence: 98%
“…However, recently published studies from the northern hemisphere provide useful pointers for future investigations. Amongst passerines in France, for example, species with the broadest ecological and thermal niches, shortest mean migration distances and largest brains were most able to adjust their phenology, indicating that specialists and long distance migrants are more at risk [84]. The migration of Barn Swallows Hirundo rustica from southern Africa appears to be constrained by the need to complete their moult before leaving their non-breeding grounds [27], [85].…”
Section: Discussionmentioning
confidence: 98%
“…Thirdly, strong neophobia delays exploitation of newly emerging resources. Thus, strong neophobic reactions in migrants may contribute to negative population developments [52] in our increasingly faster changing environment. One of the most neophobic species in our study was the rusty blackbird.…”
Section: Discussionmentioning
confidence: 99%
“…Resource use, both habitat and diet, together with average 1st clutch laying based, in most cases, on changes in photoperiod (Dawson 2008) though it has been suggested that climatic conditions on their journey to the breeding grounds may also impact species ' ability to adjust their phenology (Moussus et al 2010). Resource use, both habitat and diet, together with average 1st clutch laying based, in most cases, on changes in photoperiod (Dawson 2008) though it has been suggested that climatic conditions on their journey to the breeding grounds may also impact species ' ability to adjust their phenology (Moussus et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…moult, migration, breeding) take place at the most appropriate time of the year (Stenseth and Mysterud 2002, Bradshaw and Holzapfel 2006, Dawson 2008, Carey 2009). Strong selection pressure for matching off spring needs with peak food abundance and minimizing the cost of reproduction at the egg-laying stage can result in fl exibility and diff erential responses amongst a range of species traits (Visser 2008, Carey 2009, Moussus et al 2010. If changes in environmental conditions (due either to climate change or habitat transformation) alter the optimal timing for breeding, species ' adaptation potential will depend on their ability to alter their phenology.…”
mentioning
confidence: 99%
See 1 more Smart Citation